Determinants of adoption of the rice crop manager system among farmers in Pangasinan, Philippines - Contillo, Gerry (Animo Repository, 2019)
Information and Communication Technology (ICT) interventions had been construed as an effective and efficient means of reaching out to farmers, particularly in remote areas, to offer the technology at their doorsteps. The Rice Crop Manager (RCM) is one such intervention and was envisioned to help farmers in decision making and increasing farm productivity. However, its recommendations are not readily adopted by the farmers, although their benefits are evident from the initiators' perspective. This paper attempts to assess RCM contribution in rice production, particularly among its users. Thus, this paper evaluates the functionality and determine success indicators influencing the adoption of RCM. Respondents include farmers officially registered as members of the RCM and technicians of the province of Pangasinan. This study is anchored on the Technology Acceptance Model (TAM), which provided the theoretical foundation in the conduct of the study. A mixed method consisting of different approaches, such as surveys, interviews, focus group discussions, and document analysis was employed. Results revealed that the p-values lesser than the normal alpha level of 0.05 evidence Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Source of Water, and Technology Anxiety have a significant influence on the attitude to adopt RCM. Also, the PEOU, PU, the availability of technical services, source of fertilizer, and implementation are factors mitigating technology anxiety among farmers. On this basis, it is recommended that the government revisit policies and actions in the implementation of the RCM and strengthen support to facilitate nationwide adoption. © 2019 IEEE.